Ficolin-2: A potential immune-related therapeutic target with low expression in liver cancer - Wang, Li-ting; Zeng, Qiu-ling; Jiang, Shao-lan; Chen, Zhen-yu; Wang, Xiao-ling; Li, Ling; Li, Xiaolong (Frontiers in Oncology, 2022)
Objective: To further the role of FCN2 in the evolution and course of hepatocellular carcinoma (HCC) and to assist in the evolution of innovative HCC therapeutics.Methods: Oncomine, GEPIA, TISIDB, UALCAN, UCSC, R package, Kaplan–Meier technique, Cox regression analysis, LinkedOmics, Pearson relationship, and nomogram were used to investigate the prognostic value of FCN2 in HCC. Co-expressed genes were screened. A protein-protein interaction network was created using the STRING database. Finally, immunohistochemistry was utilized to establish FCN2 expression in HCC tissues, and a pan-cancer study centered on HCC-related molecular analysis was employed to look for a link between FCN2 and immune infiltration, immune modulators, and chemokine receptors.Results: In HCC tissues, FCN2 expression was observed to be lower than in normal tissues. This was connected to the HCC marker alpha-fetoprotein, showing that FCN2 is involved in the development and progression of cancer. It may act through Staphylococcus aureus infection, lectins, and other pathways. Furthermore, at the immune level, the expression of FCN2 in HCC is associated with some immune cell infiltration, immunomodulators, and chemokine receptors.Conclusion: FCN2 may be an immune checkpoint inhibitor for HCC, making a breakthrough in the treatment of HCC.